As políticas quantificadoras da educação e as "novas" formas de exclusão : os "inclassificáveis". - Bassani, Elizabete (2013)
Several official documents issued by the Brazilian federal, state and municipal governments nowadays insist on presenting data about the Brazilian education that show advances in the quality of elementary public schools. However, a number of studies show that even though more than 90% of Brazilian children at school age are included in elementary education, the precariousness of these schools does not even allow these children to learn how to read and write. In order to learn about the routines of these schools, this study aims at understanding how “school failure” is configured in a public elementary school in the City of Vitória, ES, Brazil, which is subject to a quantitative school assessment policy and its consequences to students and families. I chose to investigate an elementary school in Vitória that received one of the lowest scores for municipal IDEB (Brazilian Basic Education Development Index) in 2009/2010. Through an ethnographic and phenomenological case study, I monitored a whole school year of an 8th grade/9th year classroom and, particularly, one student considered to have “low index of school performance”. In this study a searched for answers to the following questions: How is school failure configured in Brazilian public schools today? Which current policies focus on "students with low performance" in these schools? Which strategies are used by schools so that their students’ performance indices increase? How can these students participate in an educational process that prevents them from learning? What is the relationship between the school and these students' families? The results obtained were presented through a consistent description of the case study and the final analysis was developed from four themes: 1) Individualization and no commitment at PAC school: the uncategorizable ones; 2) devaluation of teachers; 3) not learning as a result of not teaching; 4) Wellington’s Family and the PAC school: from school representation to routine experienced.